A convenient and eco-friendly cerium(III) chloride-catalysed synthesis of methoxime derivatives of aromatic aldehydes and ketones - Cortés, Iván (2018)
The use of CeCl3·7H2O as an efficient and eco-friendly promoter for the convenient synthesis of methoximes derived from aromatic aldehydes and ketones, is reported. The transformations entail the use of equimolar amounts of MeONH2·HCl and NaOAc in EtOH at 50°C, and no special precautions are needed with regard to the presence of oxygen. The scope and limitations of the transformation were studied and a reaction mechanism was proposed.